2002
DOI: 10.1046/j.1439-0426.2002.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of aquatic pollution in Lake Maryut on the African sharptooth catfish, Clarias gariepinus (Burchell, 1822)

Abstract: Some aspects of the physiology and biochemistry of the African sharptooth catfish, Clarias gariepinus (Burchell, 1822), were studied along with an array of physicochemical characteristics of the water in Lake Maryût, Egypt. Data were compared to those of a reference fish hatchery. At least 11 of the conventional water pollutants (Cd, Cu, Fe, Pb, Mn, Hg, Ni, Zn, turbidity, chemical oxygen demand and ammonia nitrogen) were elevated in the most polluted main basin of the lake. In turn, serologic analysis of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…In our work, decreased activity of serum ChE, which shows the hipocholinesterasemia, may be the consequence of induced-liver dysfunction due to heavy metal toxicity. The present finding is in agreement with the observation of Adham (2002) who found that serum ChE activity decreased in Clarias gariepinus in water polluted by, especially, heavy metals (Cd, Pb, Mn, Hg, Ni). The researcher concluded that ChE is synthesized by liver cells, which might be chronically injured in C. gariepinus due to water pollution.…”
Section: Resultssupporting
confidence: 94%
“…In our work, decreased activity of serum ChE, which shows the hipocholinesterasemia, may be the consequence of induced-liver dysfunction due to heavy metal toxicity. The present finding is in agreement with the observation of Adham (2002) who found that serum ChE activity decreased in Clarias gariepinus in water polluted by, especially, heavy metals (Cd, Pb, Mn, Hg, Ni). The researcher concluded that ChE is synthesized by liver cells, which might be chronically injured in C. gariepinus due to water pollution.…”
Section: Resultssupporting
confidence: 94%
“…With respect to this parameter, Adham (2002) found high serum creatinine values in populations of fish (C. gariepinus) living in polluted environments. These values have been associated with a physiological imbalance due to renal failure and/or an increase in the catabolism of the muscle tissue.…”
Section: Discussionmentioning
confidence: 97%
“…Transaminases GOT and GPT are liver-specific enzymes, which are a more sensitive measure of hepatotoxicity and histopathalogic changes, can be assessed within a shorter time in teleost fish (Balint et al1997). Increases or decreases in GOT and GPT activity levels are suggested as reflecting tissue damage in liver, kidney, and gill (Oluah 1999;Venkateswara 2006a, b) and in liver disfunction (Adham 2002). The liver GOT enzyme activity of fish exposed to 0.043-0.142 mg/l of methomyl showed a declining tendency at 24 h. Venkateswara (2006a, b) also observed decreased transaminase activity (GPT and GOT) in liver and gill of tilapia, Oreochromis mossambicus, exposed to 0.017 mg/l of novel organophosphorus insecticides, 2-butenoic acid-3-(diethoxyphosphinothioyl) methyl ester (RPR-II), and 1.15 mg/l of monocrotophos, respectively.…”
Section: Discussionmentioning
confidence: 99%